Therapeutic effect of proprioceptive dolphin assisted activities on health-related quality of life and muscle tension, biomechanical and viscoelastic properties in major depressive disorder adults: case analysis - Kreivinienė, Brigita; Šaltytė-Vaisiauskė, Laura; Mačiulskytė, Sonata (Frontiers in Human Neuroscience, 2025)
IntroductionThe case analysis method is widely used in evaluating dolphin assisted activities due to the lack of research participants. Despite other present diagnostic features adults with major depressive disorder experience psychomotor changes, dysphoria, anhedonia, impaired concentration, and suicidal thoughts. Increasing studies assess the positive effect of proprioceptive exercises in various depressive cases.Methods14 adults diagnosed major depressive disorder included in this case study between September 2022 to April 2024. A two-week proprioceptive dolphin assisted activity program was applied for each with a two-day break after half applied activities, in total 10 activities for each were organised. Proprioceptive dolphin assisted activities varied from heavy muscle work to muscles and joints pressure which was held in a special therapeutic pool, where adults wore wetsuits. The SF—36 scale was used, with levels of QoL compared among: (a) before dolphin assisted activities, (b) after two-week proprioceptive dolphin assisted activities, (c) in a year after two-week proprioceptive dolphin assisted activities. The MyotonPro portable device was used for measuring muscle tension, biomechanical and viscoelastic properties each day of participation: (a) before dolphin assisted activities and (b) after dolphin assisted activities. The MyotonPro was applied to measure the upper (descending) part of the trapezius muscle, lateral part of the deltoids muscle, middle point of the flexor carpi radialis muscle, middle point of the long head of the biceps brachii muscle, the gastrocnemius muscle (plural gastrocnemii), and quadriceps femoris muscle.ResultsThe measuring results of SF—36 scale showed statistically significant changes in 5 subscales out of 8 (Friedman’s test p-value less than 0.05) and in one more scale a partially significant change (p < 0.1). The physical activity that increased after dolphin therapy (from 68.5 to 85) remained the same in one year. There were no statistically significant changes in role limitations due to physical health. However, role limitations due to emotional problems and partially significant changes were recorded, the situation slightly worsened a year later, but there was no statistically significant deterioration. The non-parametric Wilcoxon test was used to compare two dependent samples measured by the MyotonPro. Although the improvement was recorded in almost all muscle groups, statistically significant changes were observed only in trapezius muscle md p right, measuring stiffness, relaxation and creep; trapezius md p left measuring frequency, stiffness, relaxation and decrement; and deltoids muscle left, measuring frequency, stiffness and relaxation, i.e., the p-values of Wilcoxon test are less than 0.05.ConclusionTwo-weeks of proprioceptive dolphin assisted activities for adults with major depression have statistically significant long-term change in better physical parameters. Emotional betterment parameters were less stable. The quick reactivity of trapezius muscle revealed that dolphin assisted activities acts as stress relief, and deltoids muscle as relief of negative emotions, such as fear and anger.